1994
DOI: 10.1007/bf00241098
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of [3H]brevetoxin binding to voltage-dependent sodium channels in adrenal medullary cells

Abstract: We have previously reported that in bovine adrenal chromaffin cells Ptychodiscus brevis toxin-3 (PbTx-3) does not alter the veratridine-induced 22Na influx when given alone, but increases the influx of 22Na when co-applied with either alpha- or beta-scorpion venom (Wada et al. 1992). In the present study, we characterized [3H]PbTx-3 binding in bovine adrenal chromaffin cells. [3H]PbTx-3 binding was saturable, reversible and of high-affinity with an equilibrium dissociation constant (Kd) of 32.0 +/- 4.9 nmol/l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…Either α (site 3 toxin)-, or β (site 4 toxin)-scorpion venom, or PbTx-3 (site 5 toxin) (Yuhi et al 1994) had per se little effect, but remarkably enhanced veratridine (site 2 toxin)-induced 22 Na influx even in riluzole-exposed cells in a similar manner, as in nonexposed cells; although absolute values of 22 Na influx caused by these toxins/venoms were lower in riluzole-exposed cells, this reduction was due to the inhibition of veratridine-induced 22 Na influx by riluzole. These results support the notion that an occupation of the veratridine site by riluzole per se does not impair cooperative interactions between these distinct functional peptide segments of Na channel α-subunit (Trainer et al 1994(Trainer et al , 1996Rogers et al 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Either α (site 3 toxin)-, or β (site 4 toxin)-scorpion venom, or PbTx-3 (site 5 toxin) (Yuhi et al 1994) had per se little effect, but remarkably enhanced veratridine (site 2 toxin)-induced 22 Na influx even in riluzole-exposed cells in a similar manner, as in nonexposed cells; although absolute values of 22 Na influx caused by these toxins/venoms were lower in riluzole-exposed cells, this reduction was due to the inhibition of veratridine-induced 22 Na influx by riluzole. These results support the notion that an occupation of the veratridine site by riluzole per se does not impair cooperative interactions between these distinct functional peptide segments of Na channel α-subunit (Trainer et al 1994(Trainer et al , 1996Rogers et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…α-Scorpion venom, which binds to site 3 between segment (S) 3-4 of domain IV (Rogers et al 1996), β-scorpion venom, which interacts with site 4 (Catterall 1992), and PbTx-3, which binds to site 5 (Yuhi et al 1994) between S5IV and S6I (Trainer et al 1994), caused only a slight increase of 22 Na influx over the basal value (Fig. 2).…”
Section: Effects Of Riluzole Verapamil and Nicardipine On Veratridimentioning
confidence: 99%
“…Klugbauer et al (1995) documented that the TTX/STX‐sensitive human neuroendocrine‐type Na channel α‐subunit (hNE‐Na) was widely distributed only among a variety of the neural crest‐derived cells, including bovine adrenal medulla. In cultured bovine adrenal chromaffin cells, our previous studies showed that the Na channel α‐subunit is structurally different from the brain II/II A Na channel α‐subunit (Yamamoto et al, 1996); the Na channels are sensitive to TTX/STX (Wada et al, 1985, 1987) but modulated by conotoxin GIIIA (Wada et al, 1990) and brevetoxin (Wada et al, 1992; Yuhi et al, 1994) in a manner different from those of Na channels in brain, sympathetic neuron, and cardiac and skeletal muscles. In cultured bovine adrenal chromaffin cells, we have shown that antiepileptic valproic acid raised α‐ and β 1 ‐subunit mRNA levels as well as cell surface [ 3 H]STX binding (Yamamoto et al, 1997), whereas insulin (Yamamoto et al, 1996) and PKA (Yuhi et al, 1996) elevated [ 3 H]STX binding without altering α‐ and β 1 ‐subunit mRNA levels (Wada et al, 1998).…”
mentioning
confidence: 99%
“…Voltage‐dependent Na channels purified from brain, skeletal, and cardiac muscles consist of the principal α‐subunit (~260 kDa) ; it may be associated with a noncovalently attached β 1 ‐subunit (~36 kDa) and a disulfide‐linked β 2 ‐subunit (~33 kDa) in some tissues and species (Catterall, 1992 ; Isom et al, 1994). The α‐subunits form the ion pore and the toxin binding sites, such as site 1 for tetrodotoxin (TTX)/saxitoxin (STX), site 2 for veratridine, and site 5 for Ptychodiscus brevis toxin (Catterall, 1992 ; Wada et al, 1992 ; Yuhi et al, 1994), and arise from multiple genes and/or their alternative splicing (Schaller et al, 1995 ; Toledo‐Aral et al, 1997). Structures of β 1 ‐subunits are rather similar among various tissues (Isom et al, 1992 ; Wallner et al, 1993 ; Makita et al, 1994, 1996 a , b ; Oh and Waxman, 1994 ; Patton et al, 1994 ; McCormick et al, 1998), and β 2 ‐subunits is expressed only in brain (Isom et al, 1995 a ).…”
mentioning
confidence: 99%
“…Conversely, 12‐ O ‐tetradecanoylphorbol 13‐acetate (TPA) or phorbol 12,13‐dibutyrate (PDBu), an activator of protein kinase C (PKC), lowered [ 3 H]STX binding by 53% with a t ½ of 4.5 h and an IC 50 of 19 n M via transcriptional/translational events ; TPA treatment (100 n M for 15 h) decreased the B max by 53% without altering the K D value (Yanagita et al, 1996). TPA treatment also attenuated veratridine‐induced maximal influx of 22 Na by 47% but did not affect the EC 50 of veratridine for 22 Na influx or an allosteric potentiation of veratridine‐induced 22 Na influx caused by P. brevis toxin‐3 (Wada et al, 1987, 1992 ; Yuhi et al, 1994 ; Yanagita et al, 1996). In the present study, we treated chromaffin cells with TPA or PDBu and measured α‐ and β 1 ‐subunit mRNA levels by northern blot analysis.…”
mentioning
confidence: 99%